Icaritin reduces prostate cancer progression via inhibiting high-fat diet-induced serum adipokine in TRAMP mice model - Wu, Xiaobo (J Cancer, 2020)
Objective: Obesity resulting from high-fat diets has a close relationship with the morbidity and mortality associated with Prostate cancer (PCa) in males. The anti-cancer role of Icaritin (ICT, a traditional Chinese herbal medicine) has been reported in several types of cancer including PCa. Adipokines are novel adipocyte-specific secretory protein, which plays a key role in the development of various diseases including obesity, diabetes, atherosclerosis, and cancer. However, the function of ICT and the molecular mechanisms underlying its role in PCa regression through modulation of adipokines have not been studied. Here, we assessed the anti-cancer properties of ICT under the influence of human epidermal growth factor receptor type 2 (HER2) pathway modulating adipokines in obese PCa models. Materials and Methods: In this study, we used transgenic adenocarcinoma of mouse prostate (TRAMP), a well-established animal model for the study of PCa pathogenesis. All the animals were fed on a high-fat diet (HFD with 40% fat) and divided into two groups, one received ICT solution of 30 mg/kg body bwt (i.p) while the other group served as control without any ICT treatment. The mortality rate, tumor formation and fat ratio were assessed by histopathological and magnetic resonance analysis at different time points of 20(th), 24(th) and 28(th) weeks. The protein expression of HER2 and serum levels of adipokines were measured using western blotting, IHC and multiplex immunoassays. The PCa grade in 12 TRAMP mice were longitudinally evaluated to visualize PCa development and progression upon post-surgery using PET/CT scanning. Results: We observed that ICT treatment significantly reduces the total mortality rate of TRAMP mice (p = 0.045) and the percentage of prostate intraepithelial neoplasia (PIN) or PCa (p = 0.029). Interestingly, significantly decreased levels of leptin (p = 0.006 @20(th) wk) and the elevated levels of adiponectin (p = 0.030 @20(th) wk) were observed in different subgroups upon ICT treatment in a time-dependent manner. In addition, a decrease level of HER2 (p = 0.032 @28(th) wk) and an elevated level of PEA3 (p = 0.014 @28(th) wk) were also detected in ICT treated group. The PET/CT-based imaging showed that ICT vs non-ICT treated mice had different standard uptake value and metastasis. Discussion and Conclusion: Our results showed potent anti-cancer properties of ICT through the modulation of adipokine secretion may alter the expression and activation of HER2 pathway as an alternative mechanism to prevent PCa progression. Altogether, our findings indicate that ICT could be a promising cancer preventive agent with the potential to target and eradicate tumor cells in obese PCa patients.